Fasting mitigates immediate hypersensitivity: a pivotal role of endogenous D-beta-hydroxybutyrate - Nakamura, Shigeru (BioMed Central, 2014)
BACKGROUND: Fasting is a rigorous type of dietary restriction that is associate with a number of health benefits. During fasting, ketone bodies significantly increase in blood and become major body fuels, thereby sparing glucose. In the present study, we investigated effects of fasting on hypersensitivity. In addition, we also investigated the possible role of D-beta-hydroxybutyrate provoked by fasting in the attenuation of immediate hypersensitivity by fasting. METHODS: Effects of fasting on systemic anaphylaxis were examined using rat model of toluene 2, 4-diisocyanate induced nasal allergy. In addition to food restriction, a ketogenic high-fat and low-carbohydrate diet that accelerates fatty acid oxidation and systemic instillation of D-beta-hydroxybutyrate were employed to elevate internal D-beta-hydroxybutyrate concentration. We assessed relationship between degranulation of rat peritoneal mast cells and internal D-beta-hydroxybutyrate concentration in each treatment. Changes in [Ca(2+)]i responses to compound 48/80 were analyzed in fura 2-loaded rat peritoneal mast cells derived from the ketogenic diet and fasting. RESULTS: Immediate hypersensitivity reaction was significantly suppressed by fasting. A significant reduction in mast cells degranulation, induced by mast cell activator compound 48/80, was observed in rat peritoneal mast cells delivered from the 24 hours fasting treatment. In addition, mast cells delivered from a ketogenic diet and D-beta-hydroxybutyrate infusion treatment also had reduced mast cell degranulation and systemic D-beta-hydroxybutyrate concentrations were elevated to similar extent as the fasting state. The peak increase in [Ca(2+)]i was significantly lower in the ketogenic diet and fasting group than that in the control diet group. CONCLUSIONS: The results of the present study demonstrates that fasting suppress hypersensitivity reaction, and indicate that increased level of D-beta-hydroxybutyrate by fasting plays an important role, via the stabilization of mast cells, in suppression of hypersensitivity reaction.